UJI COBA PROFIL AUS UNTUK MENGURANGI KEAUSAN FLENS RODA GERBONG KKBW KA BABARANJANGK - Dahlan, Dahlan; Soemantri, Satryo (Mesin, 2002)
This research aims at finding out the impact of the change of wheel-tread profile from conical profile of 1:40 to worn profile of ORE S 1002 against the wheel wear rate of the cars. To find out the impact of the change of the wheel-tread profile on the ride quality, ride index is measured at the initial stage of the test. The result shows that the ride index value â horizontal as well as vertical â of the test car is better than that of the reference cars. The wheel wear rate of the test car with worn profile is much lower than that of the reference cars. The lifetime of the reference carsâ wheels is around 40 months (Â± 458,182 km), while the test car with worn profile is estimated to reach 80 months (Â± 916,364 km).